2004
DOI: 10.5650/jos.53.399
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Molecular Species of Core Lipids from the Order Thermoplasmales Strains Depends on the Growth Temperature

Abstract: The order Thermoplasmales includes the wall-less strains in the Archaea. The genus Thermoplasma (two species), the genus Picrophilus (two species), and the genus Ferroplasma (one species) are present. The strains of Thermoplasma include the thermophilic acidophile (T. acidophilum grows between 45 and 62 , optimum 59 , pH 1~4, optimum 1~2 (1); T. volucanium does between 33 and 67 , optimum 60 , pH 1~4, optimum 2 (2)) and the cells are surrounded by a single triple-layer membrane, 5~10 nm thick. The family Picro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 14 publications
7
51
0
Order By: Relevance
“…In cases where the group I Crenarchaeota are the dominant source for these GDGTs, such as in most marine environments and certain lake environments, it was shown that the relative distribution of GDGTs I to VI is controlled predominantly by temperature, i.e., with increasing temperature, there is an increasing amount of GDGTs with cyclopentyl moieties (43,50). A similar phenomenon has been demonstrated for hyperthermophilic archaea (10,14,61,62).In addition to these archaeal GDGTs, analysis of soils and peats revealed the abundant presence of GDGTs with nonisoprenoid carbon skeletons (GDGTs XII to XVI) (19,49,72,73). Based on the stereochemistry of the glycerol group and their environmental distribution, Weijers et al (72) showed that they are not derived from archaea but are produced by anaerobic bacteria.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In cases where the group I Crenarchaeota are the dominant source for these GDGTs, such as in most marine environments and certain lake environments, it was shown that the relative distribution of GDGTs I to VI is controlled predominantly by temperature, i.e., with increasing temperature, there is an increasing amount of GDGTs with cyclopentyl moieties (43,50). A similar phenomenon has been demonstrated for hyperthermophilic archaea (10,14,61,62).In addition to these archaeal GDGTs, analysis of soils and peats revealed the abundant presence of GDGTs with nonisoprenoid carbon skeletons (GDGTs XII to XVI) (19,49,72,73). Based on the stereochemistry of the glycerol group and their environmental distribution, Weijers et al (72) showed that they are not derived from archaea but are produced by anaerobic bacteria.…”
supporting
confidence: 53%
“…In cases where the group I Crenarchaeota are the dominant source for these GDGTs, such as in most marine environments and certain lake environments, it was shown that the relative distribution of GDGTs I to VI is controlled predominantly by temperature, i.e., with increasing temperature, there is an increasing amount of GDGTs with cyclopentyl moieties (43,50). A similar phenomenon has been demonstrated for hyperthermophilic archaea (10,14,61,62).…”
supporting
confidence: 52%
“…However, when values of TEX 86 are calculated from GDGTs from cultured Crenarchaeota (50,51;Boyd et al,unpublished) and are compared to marine environmental samples, the slopes of these temperature relationships are not the same. If universal, the TEX 86 relationship would require that GDGT-1 disappear above 36 to 48°C (42,43), and thus its presence in cultures and geothermal springs above 65°C (Table 1) (36,61) indicates that other environmental or community variables also influence archaeal GDGT distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Here we attempted to minimize any such bias by limiting the analysis to samples in which a minimum of five (and usually six or seven) of the nine GDGTs could be identified, with one exception (Monarch Geyser; just three GDGTs). The same criterion was not applied to the cultured samples, as we believe the limited GDGT distributions observed in these samples are real (6,11,16,32,50,51;Boyd et al,unpublished).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation